2019
DOI: 10.3390/e21090893
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Autonomic and Central Nervous System Activity by Permutation Entropy during Short Sojourn in Antarctica

Abstract: The aim of this study was to monitor acute response patterns of autonomic and central nervous system activity during an encounter with Antarctica by synchronously recording heart rate variability (HRV) and electroencephalography (EEG). On three different time-points during the two-week sea journey, the EEG and HRV were recorded from nine male scientists who participated in “The First Turkish Antarctic Research Expedition”. The recordings were performed in a relaxed state with the eyes open, eyes closed, and du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…The handful of summer Antarctic expedition research studies frequently finds evidence of lower sleep quality 25 , probably resulting from the disruption of circadian rhythms 4 , 26 , and social influences emphasized by the isolated environment 26 28 . Some studies measured heart rate and its variability, finding mostly statistically nonsignificant changes between timepoints 5 , 29 31 . One study found increase in mean heart rate, increase in high-frequency and decrease in low-frequency heart rate variability 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The handful of summer Antarctic expedition research studies frequently finds evidence of lower sleep quality 25 , probably resulting from the disruption of circadian rhythms 4 , 26 , and social influences emphasized by the isolated environment 26 28 . Some studies measured heart rate and its variability, finding mostly statistically nonsignificant changes between timepoints 5 , 29 31 . One study found increase in mean heart rate, increase in high-frequency and decrease in low-frequency heart rate variability 32 .…”
Section: Introductionmentioning
confidence: 99%